Environmental and Parental Determinants of Student Learning Behavior in Bandar Lampung High Schools Survey - Permata Nurul Insa; Adrilighta Roma S; Qurratu Aini Zahra; Nabiila Chairunissa Anjani (Penerbit Goodwood, 2026)
Purpose: Environmental conditions and parental education patterns are consistently documented determinants of student learning behavior. This study examines environmental factors and parental education patterns in shaping learning behavior and truancy risk among senior high school students in Bandar Lampung, Indonesia.Research Methodology: A descriptive quantitative survey collected data from 25 students across three Bandar Lampung senior high schools, selected through purposive sampling. An eight-item questionnaire administered via Google Form measured responses on a four-point Likert scale across five domains: school environment, academic burden, peer environment, parental attention-seeking, and peer behavioral influence.Results: Most students (88%) maintained academic participation despite disliking teachers, indicating resilient learning orientation. Peer behavioral influence was the most prevalent risk factor, with 60% reporting rude language use attributable to peers. Peer-pressured truancy for leisure or substance use was rejected by 72–88% of respondents, and 88% rejected parental-attention-seeking as a truancy motive; 79.2% rejected academic workload pressure.Conclusions: Peer behavioral influence is the most prevalent environmental risk factor for negative conduct, while most students show learning persistence and resist peer-pressured truancy; parental attention deficit was not a prevalent truancy motivation.Limitations: The small sample (n = 25) from a single city limits statistical power and generalizability; behavioral self-report was used rather than achievement outcomes; no regression was feasible.Contributions: This study documents environmental and parenting risk-factor profiles for Bandar Lampung senior high school students, informing school counseling, peer education, and parental engagement initiatives.